2010
DOI: 10.4021/jocmr2010.06.375w
|View full text |Cite
|
Sign up to set email alerts
|

Latent Toxoplasmosis in Patients With Different Malignancy: A Hospital Based Study

Abstract: BackgroundSeroprevalence of toxoplasmosis in different populations may vary according to different environments, social customs and habits. This study was designed to measure the seroprevalence of toxoplasmosis among patients with different malignancies and to ascertain the association between common risk factors and disease transmission.MethodsThis Cross-sectional study was from January to April of 2009. Four Oncology wards in Hospital Universiti Kebangsaan Malaysia (HUKM) were selected as the site for undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
3
18
0
1
Order By: Relevance
“…If immune system of a patient disrupts for any reason such as pregnancy, and immunosuppressive diseases like cancer and AIDS, reactivation of parasites in tissue cysts may occur which can be even fatal (Krick and Remington 1978;Frenkel and Escajadillo 1987). Many papers were carried out about toxoplasmosis in cancerous patients (Nimir et al 2010). Ruskin and Remington (1976)and Israelski and Remington (1993) reported that Hodgkin disease is a reason for reactivation of T. gondii in 40 percent of immunocompromised patients (Ruskin and Remington 1976;Israelski and Remington 1993).…”
Section: Discussionmentioning
confidence: 99%
“…If immune system of a patient disrupts for any reason such as pregnancy, and immunosuppressive diseases like cancer and AIDS, reactivation of parasites in tissue cysts may occur which can be even fatal (Krick and Remington 1978;Frenkel and Escajadillo 1987). Many papers were carried out about toxoplasmosis in cancerous patients (Nimir et al 2010). Ruskin and Remington (1976)and Israelski and Remington (1993) reported that Hodgkin disease is a reason for reactivation of T. gondii in 40 percent of immunocompromised patients (Ruskin and Remington 1976;Israelski and Remington 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Also it showed the presence of severe infection in some samples with toxoplasmosis and cancer patients. The presence of acute infection in previous studies mentioned above due to the nature of the studied groups some of them were members of the workers in the massacres, and the other were pregnant women while the rest were couples as well as other samples were randomly taken, especially pregnant women and those were workers in the massacres which is exposed to risk factors from workers who could be infected with acute toxoplasmosis in the current study, the presence of severe infection consistent with both Nimir and others (2015), [7] and Wang et al;, [8] who pointed to the existence of severe infection toxoplasmosis among patients of cancer and in spite of the presence of acute infection. Those patients did not show 1365 symptoms of toxoplasmosis.…”
Section: Ca19-9mentioning
confidence: 52%
“…Nimir et al [24] reported that in Malaysia, most people who were found seropositive to T. gondii infection were from rural areas and at some point of their life has consumed undercooked or raw meat. Since free-range meat products are quite commonly consumed in Malaysia and regional countries, further genotyping of local isolates of T. gondii should be carried out.…”
Section: Resultsmentioning
confidence: 99%